2020
DOI: 10.21203/rs.3.rs-23569/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization of epinephrine-soaked gauzes to address bleeding from osteotomy sites in non-tourniquet total knee arthroplasty: a retrospective cohort study

Abstract: Background Abandoning tourniquet was commenced because of the complications of tourniquet extensively used for the control of hemorrhage in total knee arthroplasty (TKA). Bleeding management is critical to acquire a relative bloodless arthrotomy interface for maximize cement fixation in non-tourniquet TKA. The purpose of this study was to investigate hemostatic and hemodynamic effects of epinephrine-soaked gauzes in cemented TKAs. Methods A retrospective cohort study of 101 patients in two groups was performed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other possibilities to consider are staged approaches, a dual attending surgery (with the goal of reduced duration of surgery), and use of surgical tools such as tourniquets, electrocautery, argon-beam coagulation, topical hemostatic agents, ultrasonic bone scalpels, and local vasoconstrictive agents 86,87 During peak blood loss, packing sponges soaked in adrenaline can be utilized. 88 Temporary aortic or intra-iliac balloon occlusions have also been demonstrated to decrease blood loss in sacral tumor resection, acetabulum fracture, joint, and hip arthroplasty. [89][90][91][92] However, this has associated risks of thrombus formation, balloon rupture, or hemodynamic ischemia.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
“…Other possibilities to consider are staged approaches, a dual attending surgery (with the goal of reduced duration of surgery), and use of surgical tools such as tourniquets, electrocautery, argon-beam coagulation, topical hemostatic agents, ultrasonic bone scalpels, and local vasoconstrictive agents 86,87 During peak blood loss, packing sponges soaked in adrenaline can be utilized. 88 Temporary aortic or intra-iliac balloon occlusions have also been demonstrated to decrease blood loss in sacral tumor resection, acetabulum fracture, joint, and hip arthroplasty. [89][90][91][92] However, this has associated risks of thrombus formation, balloon rupture, or hemodynamic ischemia.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
“…Yet, there was no consensus about the optimum dose and/or concentration of its use (concentration may range from 1:50 000 to 1:400 000). It can be infused locally, systematically or tamponade the operative bed with NE‐soaked gauzes with no significant associated AEs 9,11,22–24 …”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that there was a clinically and statistically positive effect of these agents on the reduction of blood loss related to surgery. In addition, these hemostatic agents are physiologically Justified when mindfully used 9,10,22,24,25 . Another interesting study led by Wuethrich et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations